Efektifitas Pijat Bayi terhadap Peningkatan Berat Badan Bayi di Ruang Perinatologi RSU Inanta Kota Padangsidimpuan - Sri Sartika Sari Dewi; Delfi Ramadhini; Yulinda Aswan (Universitas Baiturrahim, 2021)
The growth and development period of a baby is a golden period as well as a critical period for a person's development, namely the age of 0-12 months. It is said that the critical period is because at this time babies are very sensitive to the environment and need good nutrition and stimulation for their growth and development. Stimulation or stimulation can be done through massage which is useful to stimulate all the work of the sensory and motor systems. Massage in babies will also stimulate the vagus nerve to increase intestinal peristalsis, so that gastric emptying is faster and will stimulate the baby's appetite to eat more heartily in sufficient quantities. On the other hand, baby massage can also improve blood circulation and increase cell metabolism, so that the baby's weight will increase. The purpose of this study was to identify the effectiveness of infant massage in increasing infant weight. This research uses qualitative research with a quasi-experimental design. The number of samples in this study were 22 people in the intervention group. Sampling was done using accidental sampling. This research was conducted in the Perinatology Room of Inanta Hospital, Padangsidimpuan City. Data analysis using t-dependent test. The results of the statistical test showed that the value of p = 0.000, it can be concluded that there is a significant difference in the baby's body weight before and after the massage in the intervention group. From the results of this study, it is known that baby massage is very effective in increasing the baby's weight. so that baby massage can also be used as an intervention in midwifery care for babies so that the baby's growth and development can be achieved optimally